Risk perception of the angry elderly pedestrian - Wong, Joy Changxin (Nanyang Technological University, 2021)
Elderly pedestrian jaywalking statistics have been on the rise in Singapore. Determinants of risky pedestrian behaviour include risk perception, which in turn would be related to anger. Thus, this study sought to provide insights into the cognitive and psycho-social mechanisms that lead to risky behaviour in elderly pedestrians by studying the effects of age on trait anger (referring to general dispositional anger), pedestrian anger (referring to anger in a pedestrian-specific context) and risk perception. Structural equation modelling was employed to determine the strength and significance of the regressional links. Trait anger was found to decrease with age, while pedestrian anger increased with age. Pedestrian anger was also positively affected risk perception, while trait anger and age had no direct effects. While not fully accounting for the empirical phenomenon observed, the findings in this study contribute to the literature in the relatively novel field of pedestrian anger and raise pertinent questions about the multiple pathways through which age may affect risky behaviour. Practical recommendations for the Singapore road system are discussed.